Current Evidence on Bisphenol A Exposure and the Molecular Mechanism Involved in Related Pathological Conditions - Ylenia Della Rocca; Enrico Matteo Traini; Francesca Diomede; Luigia Fonticoli; Oriana Trubiani; Alessia Paganelli; Jacopo Pizzicannella; Guya Diletta Marconi (MDPI AG, 2023)
Bisphenol A (BPA) is one of the so-called endocrine disrupting chemicals (EDCs) and is thought to be involved in the pathogenesis of different morbid conditions: immune-mediated disorders, type-2 diabetes mellitus, cardiovascular diseases, and cancer. The purpose of this review is to analyze the mechanism of action of bisphenol A, with a special focus on mesenchymal stromal/stem cells (MSCs) and adipogenesis. Its uses will be assessed in various fields: dental, orthopedic, and industrial. The different pathological or physiological conditions altered by BPA and the related molecular pathways will be taken into consideration.